The High Time Resolution Universe pulsar survey - VIII. The Galactic millisecond pulsar population - Levin, L.; Bailes, M.; Barsdell, B.; Bates, S.; Bhat, Ramesh; Burgay, M.; Burke-Spolaor, S.; Champion, D.J.; Coster, P.; D'Amico, N.; Jameson, A.; Johnston, S; et al. (Wiley-Blackwell Publishing Ltd., 2013)
We have used millisecond pulsars (MSPs) from the southern High Time Resolution Universe (HTRU) intermediate latitude survey area to simulate the distribution and total population of MSPs in the Galaxy. Our model makes use of the scalefactor method, which estimates the ratio of the total number of MSPs in the Galaxy to the known sample. Using our best-fitting value for the z-height, z= 500 pc, we find an underlying population of MSPs of 8.3(±4.2)× 104 sources down to a limiting luminosity of Lmin= 0.1 mJy kpc2 and a luminosity distribution with a steep slope of d log N/d log L= −1.45 ± 0.14. However, at the low end of the luminosity distribution, the uncertainties introduced by small number statistics are large. By omitting very low luminosity pulsars, we find a Galactic population above Lmin= 0.2 mJy kpc2 of only 3.0(±0.7) × 104 MSPs. We have also simulated pulsars with periods shorter than any known MSP, and estimate the maximum number of sub-MSPs in the Galaxy to be 7.8(±5.0) × 104 pulsars at L = 0.1 mJy kpc2. In addition, we estimate that the high and low latitude parts of the southern HTRU survey will detect 68 and 42 MSPs, respectively, including 78 new discoveries. Pulsar luminosity, and hence flux density, is an important input parameter in the model. Some of the published flux densities for the pulsars in our sample do not agree with the observed flux densities from our data set, and we have instead calculated average luminosities from archival data from the Parkes Telescope. We found many luminosities to be very different than their catalogue values, leading to very different population estimates. Large variations in flux density highlight the importance of including scintillation effects in MSP population studies.